MiR‐3146 induces neutrophil extracellular traps to aggravate gout flare. Issue 11 (4th October 2021) - Shan, Lizhen; Yang, Di; Feng, Fabo; Zhu, Danjie; Li, Xiaolin
Abstract: Background: Gout is an inflammatory arthritis and is characterized by the accumulation of deposited monosodium urate (MSU) crystals in the joints. miRNAs may act as key regulators of gout pathogenesis. The aim of our study was to explore the underlying role and molecular mechanism of miR‐3146 in the formation of neutrophil extracellular traps (NETs) during the pathogenesis of gout. Methods: The expression of miR‐3146 and sirtuin 1 (SIRT1) was determined by real‐time reverse transcription‐polymerase chain reaction and Western blot, respectively. The luciferase reporter assay was performed to identify the targeting relationship between miR‐3146 and SIRT1. Reactive oxygen species (ROS) production was detected by fluorescent staining. NETs formation was demonstrated via immunofluorescence staining and ELISA method. Gout model was induced in rats to verify the effects of miR‐3146 inhibition on histopathological changes and NETs. Results: Here, we found miR‐3146 expression was dramatically increased in neutrophils of patients with gout, which was accompanied with the higher levels of NETs. MSU crystals significantly increased miR‐3146 expression and ROS production in neutrophils. The NETs process was also triggered by MSU crystals. Furthermore, we verified the interaction between miR‐3146 and SIRT1. Additionally, antagomir‐3146‐based therapy effectively inhibited the formation of NETs in rats with gout. Conclusion: Our findings indicated that miR‐3146‐mediated NETs formation may play a potential role in the pathogenesis of gout. These results suggested that miR‐3146 could be used as a potential therapeutic target for the treatment of gout. Abstract : miR‐3146 is significantly upregulated in patients with gout. The expression of miR‐3146 in patients with gout and healthy volunteers (A); NETs formation was assessed by circulating MPO‐DNA capture ELISA method (B) and representative immunofluorescence staining of Ly6G (scale bars show 25‐mm intervals; magnification ×40) (C); The ROS production (D), the mRNA and protein levels of SIRT1 (E, F) and the serum levels of IL‐8 and IL‐1β (G) were determined. Data from at least three independent experiments were expressed as mean ± SD. ** p < 0.01 versus healthy group.